Sore throat. Crossing problems and finding solutions - E.Yu. Radtsig; A.V. Gurov (LCC «Medicine-Inform», 2022)
E.Yu. Radtsig1, A.V. Gurov1,2 1Pirogov Russian National Research Medical University, Moscow, Russian Federation 2L.I. Sverzhevskiy Research Clinical Institute of Otorhinolaryngology, Moscow, Russian Federation The article presents a brief review of the current issues relating to the treatment of acute infectious inflammatory diseases associated with sore throat. Painful throat is one of the most common reasons for the administration of systemic antibacterial drugs as a baseline therapy which, in turn, may facilitate a rise in antibiotic resistance. Recently the focus has shifted to the antibacterial therapy impact on the qualitative and quantitative composition of the microbiota. The review elucidates the opportunities of successful etiotropic therapy amid a low risk of the antibiotic resistance development and a lack of the adverse effects on the oropharyngeal microbiota. Updated information is provided characterizing the pharmacological activity of a bacterium-produced non-ribosomal antimicrobial peptide Gramicidin S and Cetylpyridinium chloride, an antiseptic agent. The highest potency of topical medications can be achieved due to the combined action of multiple synergis tic components. A potential combined use of Gramicidin S and Cetylpyridinium chloride is discussed in the review from the standpoint of the risk of antibiotic resistance and the impact on microbiota. The authors conclude that for the treatment of infectious inflammatory diseases of the upper respiratory tract associated with sore throat it is advisable to select biocenosis-saving topical etiotropic therapy. Keywords: Gramicidin S, non-ribosomal antimicrobial peptides, Cetylpyridinium chloride, topical etiotropic therapy, bactericidal activity, antibiotic resistance, microbiocenosis-saving therapy, pharyngitis, tonsillopharyngitis. For citation: Radtsig E.Yu., Gurov A.V. Sore throat. Crossing problems and finding solutions. Russian Journal of Woman and Child Health. 2022;5(3):228-236 (in Russ.). DOI: 10.32364/2618-8430-2022-5-3-228-236.